2019
DOI: 10.3233/jad-190090
|View full text |Cite
|
Sign up to set email alerts
|

Locus Coeruleus Degeneration Induces Forebrain Vascular Pathology in a Transgenic Rat Model of Alzheimer’s Disease

Abstract: Noradrenergic locus coeruleus (LC) neuron loss is a significant feature of mild cognitive impairment and Alzheimer’s disease (AD). The LC is the primary source of norepinephrine in the forebrain, where it modulates attention and memory in vulnerable cognitive regions such as prefrontal cortex (PFC) and hippocampus. Furthermore, LC-mediated norepinephrine signaling is thought to play a role in blood-brain barrier (BBB) maintenance and neurovascular coupling, suggesting that LC degeneration may impact the high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 132 publications
(199 reference statements)
1
50
0
Order By: Relevance
“…Astrogliosis itself, which is significantly increased by LC loss (Heneka et al, 2006;Kelly et al, 2019) is often associated with neuroinflammation, and it might also further interfere with BBB permeability, as reactive astrocytes could have lost at least in part their supporting role on BBB as shown by Kalinin et al (2006).…”
Section: Neurovascular Unit-related Neuroinflammationmentioning
confidence: 99%
“…Astrogliosis itself, which is significantly increased by LC loss (Heneka et al, 2006;Kelly et al, 2019) is often associated with neuroinflammation, and it might also further interfere with BBB permeability, as reactive astrocytes could have lost at least in part their supporting role on BBB as shown by Kalinin et al (2006).…”
Section: Neurovascular Unit-related Neuroinflammationmentioning
confidence: 99%
“…Finally, it is worth noting that Betts and colleagues observed a relation between CSF amyloid and LC-CR, in line with preclinical data. Indeed in animal model of AD, LC damage has been associated to increased amyloid burden [29,33], in parallel with a more severe neuroinflammation [30] and to worse neurovascular pathology [31], and neuropathological post-mortem data in humans support these observations [10,100]. Since neuroinflammatory, amyloid and vascular burdens can be evaluated in vivo by specific neuroimaging approaches (e.g., TSPO-specific PET tracer for neuroinflammation [101], amyloid PET and specific MRI sequences for amyloid and vascular alterations, respectively), LC-MRI represents a very interesting opportunity to assess the abovementioned correlations in vivo also in AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Heneka and colleagues concluded that LC-NA may be key in promoting amyloid clearance system and in modulating microglial activity [29,30,32], and several more recent experimental studies support this hypothesis [3,[33][34][35]. Furthermore, LC impairment has also been linked to AD vascular pathology by Kelly and colleagues who observed a significant exacerbation of microvascular injury and amyloid angiopathy, in AD transgenic mice submitted to selective LC lesion [31].…”
Section: Potential Role Of Lc In the Pathophysiology In Neurodegeneramentioning
confidence: 95%
See 1 more Smart Citation
“…However, the mechanisms of amyloidosis may vary under different conditions and may also involve impaired functioning of blood vessels and blood-brain barrier. For example, it was recently shown that amyloidosis is enhanced in the frontal cortex of Tg344 rats (rats overexpressing APPswe/PS1dE9) after elimination of noradrenergic projections by anti-DBH-saporin [123]. The authors also found that cortical noradrenergic deficit was associated with compromised function of blood-brain barrier and remodeling of vessel structure, which resembled pathological stenosis.…”
Section: Alzheimer's Diseasementioning
confidence: 99%